A combined local damage index for seismic assessment of existing RC structures. (31st August 2012) - Mergos, P. E.; Kappos, A. J.
SUMMARY A new local damage index for existing RC structures is introduced, wherein deterioration caused by all deformation mechanisms (flexure, shear, anchorage slip) is treated separately for each mechanism. Moreover, the additive character of damage arising from the three response mechanisms, and the increase in degradation rate caused by their interaction, are fully taken into consideration. The proposed local damage index is then applied, in conjunction with a finite element model developed previously by the authors, to assess seismic damage response of several RC column and frame test specimens with substandard detailing. It is concluded that in all cases and independently from the prevailing mode of failure, the new local damage index describes well the damage pattern of the analysed specimens. Copyright © 2012 John Wiley & Sons, Ltd.